Mission-Based Monitoring, Evaluation and Learning (MEL) Platforms Assessment Report - and Arntson, Laura; Giannoni, Tonya; Peek, Nancy; Saarlas, Kristin (USAID, 2017)
In 2016, the Bureau of Policy, Planning and Learning (PPL) commissioned an internal stocktaking of USAID's mission-based MEL (Monitoring, Evaluation, and Learning) Platforms.